Museum der Bildenden Künste Leipzig - Jahresheft 1996. - Artinger, Kai; Beck, Rüdiger; Guratzsch, Herwig; Hartleb, Renate; Priever, Andreas; Stolzenburg, Andreas; Museum der bildenden Künste, Leipzig (Leipzig : Museum der bildenden Künste, 1997)
Achenbach, Oswald ; Begas, Reinhold ; Ebersbach, Hartwig ; Eissner, Frank ; Firit, Günter ; Grimmling, Hans-Hendrik ; Hassebrauk, Ernst ; Heller, Bert ; Hussel, Horst ; Kapr, Albert ; Kesting, Edmund ; Kuprianov, Vladimir ; Lichtenfeld, Gerhard ; Martini, Marino ; Marx, Carl ; Metzkes, Harald ; Möhwald, Otto ; Müller, Knut ; Müller, Thomas Matthaeus ; Rauch, Neo ; Richter, Hans Theo ; Schult, Frank ; Schultheiss, Arnd ; Schulz, Jeanette ; Wachter, Andreas ; Walter, Klaus ; Walther, Franz Erhard ; van der Weyden, Rogier ; Zeidler, Simone ; Zettl, Baldwin ; Schmidt-Rottluff, Karl ; Picasso, Pablo ; Haring, Keith ; Mueller, Otto ; Beckmann, Max ; Klinger, Max ; Blechen, Carl
Duits
boek